PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH BERBASIS SUSTAINABLE LIVELIHOODS DI KABUPATEN BARRU - Maharani, Dian Putri; Mahsyar, Abdul; Akbar, Muhammad Randhy (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this study is to determine the application of the Sustainable Livelihood approach in maintaining the sustainability of MSMEs in Barru Regency. This research uses a descriptive qualitative research type. Data collection techniques through interviews, documents and direct observation. The data analysis technique uses